(untitled) (Bangladesh Journal of Child Health, 2020)
Background: Neonatal death is a major barrier to improve child survival in Bangladesh. This study assessed the patterns of neonatal admissions, causes of deaths and associated risk factors to prioritize and design interventions to improve quality of services. Materials & Methods: This study was conducted at the Satkhira District Hospital, a secondary health care facility in Bangladesh. From January to December 2014 hospital records of neonatal admissions and outcomes were reviewed and analyzed. Risk factors were determined by logistic regression analysis. Results: A total of 2,632 neonates were admitted during the period. More than one-third had admission bodyweight below 2500 grams. The leading causes of admissions were perinatal asphyxia (39.6%), prematurity/low-birth weight (LBW) (16.3%), pneumonia (11.9%) and sepsis (10.0%). The overall neonatal case fatality rate (CFR) was 11.7%. The main causes of neonatal deaths were perinatal asphyxia (41.6%) and prematurity/ LBW (35.8%). Most of the deaths (74.3%) occurred on first day of life. Significant risk factors for death were body weight on admission <1500 grams (OR: 17.08; 95% CI: 7.22 - 40.44; p<0.001), first day of life (OR: 7.99; 95% CI: 2.86 -22.27; p<0.001). Conclusions: The main causes of neonatal deaths were perinatal asphyxia and prematurity/LBW and most of the deaths occurred on first day of life. Bangladesh J Child Health 2019; VOL 43 (3) :138-144